Interventi di espianto e trapianto di Posidonia oceanica L. (Delile) a Rapallo e Sestri Levante a seguito di potenziamento delle opere di difesa portuale - Negri, Martina; Bernat, Paolo; Molinari , Andrea (Biologia Marina Mediterranea, 2025)
After the 2018 storm surge, interventions were planned in Rapallo and Sestri Levante (Genova, Liguria, italy) to strengthen the costal defence works and this could have interfered with some small portions of Posidonia oceanica (L.) Delile meadows. To compensate for the damage, interventions were carried out by removing a portion of the plants that would have been impacted and subsequently trasnplanting them to close areas, followed by a monitoring for apporximately 6 years. In Rapallo in 2020, 464 plants were transplanted and during the last monitoring in 2023, 235 were counted, with a survival rate of 54.5%. In Sestri Levante, in 2021 there were 545 and in the 2023 monitoring, 409 were counted, with a survival rate of 75.0%. To date, the results are consistent with the literature and the data will be collected with monitorings until 2026 to keep updating the project.